1998
DOI: 10.1148/radiology.207.1.9530297
|View full text |Cite
|
Sign up to set email alerts
|

Biliary tract carcinoma complicating primary sclerosing cholangitis: evaluation with CT, cholangiography, US, and MR imaging.

Abstract: Most biliary tract carcinomas complicating PSC can be demonstrated on imaging studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 0 publications
2
48
0
4
Order By: Relevance
“…Papillary tumours are less likely to invade the liver directly and have lower incidence of lymph-node metastasis. [9][10][11][12] In our study one case (20%) showed papillary pattern of adenocarcinoma. Most carcinomas of the gallbladder are adenocarcinomas (80-95%) as in the present study, and can be papillary, tubular, mucinous, or signet cell type.…”
Section: Discussionsupporting
confidence: 56%
“…Papillary tumours are less likely to invade the liver directly and have lower incidence of lymph-node metastasis. [9][10][11][12] In our study one case (20%) showed papillary pattern of adenocarcinoma. Most carcinomas of the gallbladder are adenocarcinomas (80-95%) as in the present study, and can be papillary, tubular, mucinous, or signet cell type.…”
Section: Discussionsupporting
confidence: 56%
“…The reported radiographic features of cholangiocarcinoma, namely, marked and progressive dilatation or stricture formation or the presence of intraductal polypoid masses, 58 are not seen in all patients with this malignancy. 55 A combination of more than one imaging procedure may have a greater diagnostic accuracy, 59 particularly when image-guided biopsies are taken. Positron emission tomography is a new, exciting technology that looks promising in the detection of small cholangiocarcinomas in patients with PSC, 60 although further studies are needed to define its role in the management of these patients.…”
Section: Malignancymentioning
confidence: 99%
“…Serum aminotransferase levels are elevated in the majority of patients with this disease (about 2-3 times upper limits of normal), but like the alkaline phosphatase can also be in the normal range [9]. CT imaging can detect thickening of the bile ducts with contrast enhancement consistent with inflammation, saccular dilatations of the intrahepatic ducts, heterogeneous bile duct dilatation, document the presence of portal hypertensive complications (i.e., varices, splenomegaly, and ascites), and can identify mass lesions [10][11][12][13][14]. Detectable auto antibodies are found in about 97% of patients with PSC [15], these auto antibodies, however, are not routinely used for the diagnosis of PSC, as they may not be present and furthermore do not correlate with disease severity or disease prognosis [16].…”
Section: Discussionmentioning
confidence: 99%